Ordinary medicine: The power and confusion of evidence (Medicine Anthropology Theory, 2016)
Medicine in the twenty-first century is constituted and propelled by the production of evidence. Once produced, the use of that evidence is complicated by features inherent in the American and global biomedical economy itself. With the exponential rise in the use of cardiac devices as my case study, this think piece traces the links among evidence-based medicine, insurance reimbursement policies, and clinical trial outcomes to reveal how evidence produced by trial findings creates treatment standards. Those standards, in turn, expand what is thought to be ‘treatable’ by reconceptualizing risk as a condition that deserves intervention. Such standards affect what physicians recommend and what patients decide to do. The essay emphasizes that evidence-based medicine can be a source of anxiety that patients and families feel when considering how to proceed. It highlights the debates, increasingly common both within and beyond the health professions, about what is actually best as we grow older. It provides an example of how, today, most deaths, even among the very old, are considered premature. In an aging society, the treatment protocols that fall under the evidence-based medicine umbrella constitute an enormous truth-making regime that determines the goals of medicine and shapes health care consumers’ quandaries about medical intervention, and especially the quandary, for those in later life, about crossing the line of too much treatment.